KEBIJAKAN ADAPTIF-STRATEGIK INDONESIA TERHADAP CHINA DALAM KASUS SUKU UIGHUR DI XINJIANG (2014–2019) - Dyah Purbo Arum Larasati; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research aims to find out the reason about why Indonesia government has not yet elevate their political pressure (act) to China in the case of Uighur ethnic cleansing in Xinjiang. This is unique for sure pondering that Indonesia quite being active in criticize the Israel colonialism towards Palestine, but nothing for Uighur, or here is means getting stagnancy. Even on the one side, the Israel–Palestine conflict is about colonialism, but it also same towards Uighur case that need the acknowledgment of human rights. The Uyghur conflict which absolutely can be seen by the news scattered in the international media, said that millions Uyghur have been detained in camps build by the Chinese government in Xinjiang province. Xinjiang itself has been known as the strategic location and rich by its oil, while Uyghur is an ethnic that origins from Proto–Turkey, they dwelled the autonomous region of Xinjiang in the Middle Asia. Uyghur have some similarities in history, culture, and religion with Turkey, also often mentioned having clash with Han as the majority ethnic in China.The Uyghur case has been un–directly summoning Indonesia citizen’s sympathy, notably those in the religious groups who demand the Indonesia government to take the strict pressure towards China. Their demands explained side by side against the other religious groups, include those commonly looks as nationalist in the government level, which further this intended to illustrate the most dominant influence in Indonesia’s foreign policy.This research uses the perspective of behavioralism which is intended to depict the situation of Indonesia’s foreign policy made by a group of decision makers which is further the product of policy itself would be based the thought of those decision makers. This research also uses the theory of adaptive–strategic foreign policy, intended to create a balance either the external or the internal pressure that Indonesia has been facing since this issue was emerged. The other relatable stuff also comes from the usage of the analysis level of group, which this one used to explain the situation and the strategic decision ignited as a product of Indonesia’s foreign policy, made based the consideration of group in the government level. Furthermore, this research uses the qualitative method, characterized by collecting and analyzing data from books, journals, articles, and news that come from various media. Keywords: foreign policy, human rights, Uyghur, Xinjiang, China, Indonesia